Reliability of clinical diagnosis of the symptomatic vascular territory in patients with recent transient ischemic attack or minor stroke. - Flossmann, E; Redgrave, J; Briley, D; Rothwell, P (2008)
BACKGROUND AND PURPOSE: Knowledge of the vascular territory of a recent transient ischemic attack or minor stroke determines appropriate investigations and the need for territory-specific interventions such as endarterectomy and stenting. However, there are few published data on the accuracy of clinical assessment of the vascular territory. METHODS: We studied agreement of clinical diagnosis of vascular territory in consecutive patients with transient ischemic attack or minor stroke with diffusion-weighted MRI who had an acute ischemic lesion(s) in a single vascular territory (determined by a neuroradiologist). Three independent neurologists (one had seen the patients, the others had a clinical summary) diagnosed the most likely vascular territory (carotid or vertebrobasilar) for each patient blind to brain imaging. RESULTS: One hundred thirty-three (28.0%) of 476 patients had a high signal lesion on diffusion-weighted imaging of whom 115 (86.5%) had a minor stroke and 18 (13.5%) a transient ischemic attack. Interobserver agreement (kappa statistic) on the territory ranged from 0.46 to 0.60. The agreement with diffusion-weighted imaging was only moderate (observer 1: kappa=0.54, 95% CI=0.36 to 0.72; observer 2: 0.48, 0.31 to 0.64; observer 3: 0.48, 0.28 to 0.67). Only the presence of visual symptoms improved the accuracy of the vascular territory diagnosis (range of kappa: 0.63 to 0.77) but not the presence of motor, speech, or sensory symptoms. Sensitivity and specificity for the diagnosis of vertebrobasilar territory ranged between 54.2% and 70.8% and 84.4% to 91.7%, respectively. CONCLUSIONS: The reliability of clinical diagnosis of the vascular territory is only moderate, highlighting the importance of sensitive brain imaging after transient ischemic attack or minor stroke. Further imaging-based research is required to determine the optimal clinical diagnostic criteria for classification of the vascular territory.